Boom and bust: Thinking through health care resource allocation in an oil economy (Medicine Anthropology Theory, 2017)
In this think piece I argue that there is an interactive relationship between physical and symbolic landscapes, and that the interplay of the two forms a ‘therapeutic landscape’. This reformulation of Gesler’s (1992) concept of the therapeutic landscape helps to make visible the relationship between utilitarian systems of natural resource extraction and notions of deservingness for care. I show how in Alberta, Canada, there was a shift in the therapeutic landscape following the late 2014 crash in the global price of oil. Alberta is an ‘oil economy’ with an economic system that is strongly dependent on its oil and gas extractive industry; its public health care system is supported in part by royalties paid by private oil companies. When the global price of oil dropped, both health policy researchers and parents of children with rare and severe genetic diseases worried that costly treatments might be valued differently in this new terrain and that patients might be deemed undeserving of such expense. The therapeutic landscape concept applied in this way becomes a tool for understanding the linkages between economies of care and the political economy of place.